2014
DOI: 10.1021/jp501249k
|View full text |Cite
|
Sign up to set email alerts
|

Free Energy Calculations for Identifying Efficient Promoter Molecules of Binary sH Hydrogen Clathrates

Abstract: To determine the stabilizing effect of different promoter molecules on the clathrate, the Gibbs free energy of fully occupied binary sH hydrogen clathrates with secondary guest molecules in the large cages is calculated with Monte Carlo simulations. The small and medium cages of sH are occupied by one H2 guest molecule. Various promoter molecules enclathrated in the large cages are considered. Simulations are conducted in the pressure range of 250–1000 atm for temperatures ranging from 233 to 273 K. We investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…H 2 hydrate was first synthesized by Dyadin et al In 2002, Mao et al found that H 2 and water mixtures form sII clathrate at 250–600 MPa and 240–249 K with a maximal H 2 storage capacity of 5.3 weight percent . H 2 can occupy the small 5 12 cages and also the larger 5 12 6 4 cages, where the larger cages can be multioccupied. To decrease the impractical pressure to stabilize the H 2 hydrate, other additives such as tetrahydrofuran (THF) are used to synthesize the hydrate, where H 2 + THF binary hydrates can form at ∼10 MPa and 280 K . However, THF molecules occupy all the larger 5 12 6 4 cages, but H 2 molecules only occupy the small 5 12 cages.…”
Section: Introductionmentioning
confidence: 99%
“…H 2 hydrate was first synthesized by Dyadin et al In 2002, Mao et al found that H 2 and water mixtures form sII clathrate at 250–600 MPa and 240–249 K with a maximal H 2 storage capacity of 5.3 weight percent . H 2 can occupy the small 5 12 cages and also the larger 5 12 6 4 cages, where the larger cages can be multioccupied. To decrease the impractical pressure to stabilize the H 2 hydrate, other additives such as tetrahydrofuran (THF) are used to synthesize the hydrate, where H 2 + THF binary hydrates can form at ∼10 MPa and 280 K . However, THF molecules occupy all the larger 5 12 6 4 cages, but H 2 molecules only occupy the small 5 12 cages.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure , the presence of the ether (c–o–c) functional group in the epoxy heterocycle significantly decreased the hydrate formation pressure substantially compared with that of pure hydrogen hydrate (above 200 MPa at 275 K).The ether functional group (c–o–c) in epoxy heterocycle compounds influenced the hydrogen bond among water molecules, which induced and changed the order of hydrogen bonding between water molecules. , The van der Waals force between thermodynamic additive molecules and water molecules is reinforced. As consequences of that, it was thermodynamically easier for epoxy heterocycles containing the ether functional group (c–o–c) to form hydrate cages with water and promote the formation of hydrogen hydrate . However, the above mentioned results indicated that 1,4-dioxane with double ether functional groups­(c–o–c) had the worst promoting effect, which may be the weakened hydrogen bond caused by the competition between double ether functional groups­(c–o–c) and water molecules.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore propose CNO and CDE as potential candidates for sH hydrogen clathrates formers. In a previous computational study 27 we have shown that the stability of sH hydrogen clathrate hydrates with these two promoter molecules demonstrates an unusually strong temperature dependence, which can be exploited if easy release of hydrogen is required.…”
Section: Distinguishing Si and Sii Clathrates Formationmentioning
confidence: 99%